Filament [compact disc] - Dessner, Bryce; Muhly, Nico; Dessner, Bryce; Muhly, Nico; Son Lux, 1979-; Glass, Philip; Son Lux, 1979- (Cedille, 2015)
Celebrated new-music sextet eighth blackbird, whose last three Cedille Records albums garnered Grammy awards, continues to soar with this album, a selection of four world premiere recordings plus a concert performance of Philip Glass's influential Two Pages.